GADAMER'İN FELSEFİ HERMENEUTİĞİNDE 'ÖNYARGI KAVRAMI ve DÜŞÜNDÜRDÜKLERİ - Ramazan Ertürk (Felsefe Dünyası)
This article aims at investigating and clarifying Hans-Georg Gadamer's concept of prejudice and also of pre-understanding and some implications of it. According to Gadamer, our concept of prejudice—as is today—is constituted by the Enlightenment thought. This concept is both an ill-founded and an ill-functioning concept. Gadamer thinks that he rehabilitates it. Here, the nature of Gadamer's rehabilitation process is examined and clarified; furthermore, some important points are proposed as the conclusions that may be drawn from Gadamer's process.